Mengembangkan Model Pembelajaran Kooperatif tipe Think Pair Share dengan pendekatan problem posing untuk meningkatkan motivasi belajar mahasiswa pada mata kuliah aljabar linier - Yohanie, Dian Devita; Samijo, Samijo (Efektor, 2016)
The purpose of this research is to know learning using collaboration of problem posing method with cooperative type Think-Pair-Share can improve student achievement of second grade-DProdi Pendidikan Matematika Universitas Nusantara PGRI Kediridalam learning matemetika material Algebra Linier. This study uses a Classroom Action Research approach (PTK) with research subjects of second grade students-DProdi Pendidikan Matematika Universitas Nusantara PGRI Kediri. The research was conducted in two cycles, using instrument in the form of RPP, student activity observation sheet, observation sheet of lecturer activity and test of student learning result. The results of research on the first cycle is the average of student achievement 69 with the highest score of 90 and the lowest score 48 with 64.70% classical completeness. While the second cycle is obtained average student achievement of 82.58 with the highest value of 100 and the lowest score 59 with 88,23% classical completeness. This shows that students' learning outcomes have increased gradually from cycle I to cycle II. With the acquisition of the above results, it can be concluded that through the implementation of collaborative learning method of problem posing with cooperative type Think-Pair-Share can improve student achievement of second grade-DProdi Pendidikan Matematika Universitas Nusantara PGRI Kediri on linear Algebra subject.